Copper Catalysts Supported on CeMnO2 for CO Oxidation in Hydrogen-Rich Gas Streams - N. Hoshyar; A. Irankhah Irankhah; M. Jafari (Iranian Journal of Chemical Engineering)
e"> The CeMnO2 supports were prepared via co-precipitation method by ammonia as precipitating agent. The CuO/CeO2 and CuO/Ce(1-x)MnxO2 (x=0.1, 0.3 and 0.5) catalysts were synthesized by wet impregnation method. The physicochemical properties of the prepared CuO/Ce(1-x)MnxO2 catalysts were characterized by N2 adsorption-desorption, powder X-ray diffraction (XRD) and programmed H2 temperature reduction (H2-TPR). The effects of Cu and Mn loading were investigated on the catalytic performance. The findings illustrated that the 7% CuO/Ce0.9Mn0.1O2 catalyst shows high activity for CO-PrOx. The high activity of 7% CuO/Ce0.9Mn0.1O2 catalyst was ascribed to high surface area of the support, synergetic effects of CuO and CeO2 and increases of the mobility of lattice oxygen in ceria by addition of MnO2. The effects of presence of H2O in the reaction feed stream, oxygen to CO ratio (λ) and gas hourly space velocity (GHSV) on the catalytic activity of 7% CuO/Ce0.9Mn0.1O2 were evaluated. It was found that the best performance of 7% CuO/Ce0.9Mn0.1O2 catalyst was obtained at λ=2, GHSV=20000 h-1 and in addition, the presence of H2O had negative effects on the activity of the catalyst. In the long term stability test, nearly 100% CO conversion was maintained for 50 h at 120°C with 70-80% CO2 selectivity.